ANALYSIS OF STRESS STATE IN UPPER LAYER OF ROAD CONCRETE PAVEMENT WITH TEMPERATURE ACTION - M. K. Pshembaev; Ya. N. Kovalev; L. I. Shevchuk (Наука и техника)
While being operated auto-road pavements are subjected to intensive mechanical impacts, ultraviolet ray irradiation, freeze-thaw temperatures, freezing and thawing, drying and moistening. Due to these actions various types of pavement distresses appear on the road pavement. The most significant and dangerous type of distresses is micro-cracks on the road surface. One of the main reasons for their formation is an action of weather and climatic factors that initiate large changes in temperature of coating surface and occurrence of large temperature gradients in the upper layer. In this context while designing and operating auto-roads it is rather essential to investigate a stress state in road surface which is caused by temperature action. Purpose of the described investigations is to determine permissible temperature gradients for cement-concrete pavements that exclude formation of micro-cracks on their surface and thickness of damaged surface layer. Calculations of road pavement have been carried out at various laws for temperature distribution in its depth. A finite difference method realized in PARUS software has been used for studying a stress state of cement-concrete auto-roads. Regularities for distribution of stresses in cement-concrete pavement of auto-roads have been obtained at various surface temperatures. Permissible temperature gradients in the upper pavement layer have been determined and thickness of the layer where micro-cracks are formed has been assessed in the paper. Strength criterion based on the process of micro-crack formation and development in the concrete has been used for calculations. Risk of micro-crack formation on the auto-road pavement depends on material strength, conditions of plate fixing and temperature gradients.